No significant steady state surface creep along the North Anatolian Fault offshore Istanbul: Results of 6 months of seafloor acoustic ranging - Sakic, Pierre; Piété, Helen; Ballu, Valerie; Royer, Jean-Yves; Kopp, Heidrunn; Lange, Dietrich; Petersen, Florian; Özeren, M. Sinan; Ergintav, Semih; Geli, Louis; Henry, Pierre; Deschamps, Anne (American Geophysical Union (AGU), 2016)
AbstractThe submarine Istanbul‐Silivri fault segment, within 15 km of Istanbul, is the only portion of the North Anatolian Fault that has not ruptured in the last 250 years. We report first results of a seafloor acoustic ranging experiment to quantify current horizontal deformation along this segment and assess whether the segment is creeping aseismically or accumulating stress to be released in a future event. Ten transponders were installed to monitor length variations along 15 baselines. A joint least squares inversion for across‐fault baseline changes, accounting for sound speed drift at each transponder, precludes fault displacement rates larger than a few millimeters per year during the 6 month observation period. Forward modeling shows that the data better fit a locked state or a very moderate surface creep—less than 6 mm/yr compared to a far‐field slip rate of over 20 mm/yr—suggesting that the fault segment is currently accumulating stress.
Keywords: [SDU.STU.TE]Sciences of the Universe [physics]/Earth Sciences/Tectonics; [SDU.STU.GP]Sciences of the Universe [physics]/Earth Sciences/Geophysics [physics.geo-ph]; [SDU.STU.TE] Sciences of the Universe [physics]/Earth Sciences/Tectonics; seismic hazard; Marmara; acoustic ranging; acoustic; North Anatolian Fault; Seafloor geodesy; [SDU.STU.GP] Sciences of the Universe [physics]/Earth Sciences/Geophysics [physics.geo-ph]; seafloor geodesy; earthquakes; Marmara Sea